Ensemble classics for bass quartet Book I For two Bb cornets and two trombones or trombone and baritone - VOXMAN, H. (Rubank Inc., 1947)
Andantino tranquillonBohemian songnChorale from die meistersingernChorus of the captives from prince igornEcho